Changing Inequalities in Rich Countries 2014
DOI: 10.1093/acprof:oso/9780199687435.003.0010
|View full text |Cite
|
Sign up to set email alerts
|

The Policy Response to Inequality: Redistributing Income

Abstract: Public social expenditure is the most commonly used proxy variable for the size of the welfare state. While this indicator has certain limitations for welfare analysis, 1 both conceptual (Esping-Andersen, 1990) and methodological (De Deken and Kittel, 2007) spending clearly matters, not least in a context of general budget austerity. The share of public social spending in GDP ranges widely across OECD and EU countries, as shown in Figure 10.1. Average social expenditure in the OECD rose rather strongly from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, such trends must be put into perspective by considering economic and socio‐demographic parameters (cf. Marx & Rie, 2014), like the proportion or number of benefit recipients.…”
Section: Welfare State Change In Sweden and Germany Since 1975mentioning
confidence: 99%
See 1 more Smart Citation
“…However, such trends must be put into perspective by considering economic and socio‐demographic parameters (cf. Marx & Rie, 2014), like the proportion or number of benefit recipients.…”
Section: Welfare State Change In Sweden and Germany Since 1975mentioning
confidence: 99%
“…This is because spending levels are a function not only of individual generosity (what benefit level does the welfare state provide to individuals) but also of need (how many individuals need assistance). Moreover, since comparative spending analyses typically measure ‘spending’ ratios (social spending/GDP), measured changes not only reflect changes in benefit commitments and the number in need but also changing macroeconomic aggregates: the state's automatic mechanisms reacting to times of crises (e.g., Marx & Rie, 2014; Reinprecht et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…and, on the other hand, on institutional features of the labor market (Salverda and Haas 2014). Previous research has shown that high levels of minimum wage protection, strong collective bargaining, more extensive public and subsidized employment, and well-developed active labor market programs, on average, are associated with higher levels of employment and smaller earnings disparities (Bassanini and Duval 2006;Marx and van Rie 2014;Sologon and O'Donogue 2014). The impact of these institutions on poverty, however, largely depends on how they affect employment and incomes of households at different points of the household income distribution (Neumark and Wascher 2002;Lang 2012;Salverda and Haas 2014;Matsaganis et al 2015;Atkinson et al 2017).…”
Section: Reconciling the Differences In The Determinants Of Poverty And Poverty Gaps At The Individual Levelmentioning
confidence: 99%
“…Comparisons typically include—but are not limited to—the extent to which, and the ways in which, these systems redistribute income. Recent overviews include those of Marx et al 2015, Marx & van Rie 2014, Wang et al 2014, Caminada et al 2012, and Lindert 2004.…”
Section: Redistribution By the State: Government Transfers And Directmentioning
confidence: 99%